Processing of Threat-related Information Outside the Focus of Visual Attention - G. Calvo, Manuel; Castillo, M. Dolores (The Spanish Journal of Psychology, 2005)
This study investigates whether threat-related words are especially likely to be perceived in unattended locations of the visual field. Threat-related, positive, and neutral words were presented at fixation as probes in a lexical decision task. The probe word was preceded by 2 simultaneous prime words (1 foveal, i.e., at fixation; 1 parafoveal, i.e., 2.2 deg. of visual angle from fixation), which were presented for 150 ms, one of which was either identical or unrelated to the probe. Results showed significant facilitation in lexical response times only for the probe threat words when primed parafoveally by an identical word presented in the right visual field. We conclude that threat-related words have privileged access to processing outside the focus of attention. This reveals a cognitive bias in the preferential, parallel processing of information that is important for adaptation.